PENGARUH DISIPLIN TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT PANCA AGRO LESTARI KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Rotua, Sari Lestari; Nas, Syakdanur; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of this research to determine the effect on the performance of labor discipline employees part of production PT Panca Agro Lestari. The population in this this research were 300 employees. The sample size of 75 people by using proportional stratified. Collecting data in this study using the technique of questionnaires. The results of this study indicate that the discipline of a positive and significant effect on the performance of employees part of production PT. Panca Agro Lestari Gansal Batang District of Indragiri Hulu.Key Words: discipline, performance